INCENTIVOS LEGALES PARA LA GENERACIÓN DE ENERGÍAS ALTERNATIVAS. ESTÍMULO O FRACASO LEGISLATIVO? - Gutawski, Roberto S.; Fernández, Marisa I.; Plessen, Antonio R.; Derna, Juan A. (Salão do Conhecimento, 2013)
Resumo